PECULIARITIES OF PUBLIC PROCUREMENT DEVELOPMENT IN UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article analyzes the features of public procurement in Ukraine and their compliance with EU standards; factors that affect their effectiveness; problems that exist in Ukraine when conducting tender procurement; rights and responsibilities of the country's controlling structures in the field of public procurement. The purpose of the article is to reveal the features and problems of public procurement in Ukraine and identify ways to overcome them. Accordingly, the objectives of the article are to substantiate the directions of reforming the mechanism of public procurement in Ukraine, taking into account the experience of EU countries; identification of financial features of public procurement after the entry into force of the new version of the Law of Ukraine "On Public Procurement"; study of forms of financial responsibility of public procurement participants in Ukraine and their effectiveness.Public procurement is an important tool for regulating supply and demand for specific types of products, as they are the purchase of goods, works and services from the state and local budgets. Due to this, it is important to achieve efficient use of budget funds allocated for public procurement in Ukraine, which is not happening yet. Therefore, to increase the transparency and efficiency of the use of these funds in our country, it is advisable to study the experience in this matter of EU member states, especially Poland.An in-depth analysis of the experience of public procurement in the EU will reveal effective approaches to their implementation in Ukraine, as the main task of reforming public procurement in our country is to implement an effective system in accordance with the principles and approaches used by EU countries. efficiency and transparency of the procurement procedure.It is also necessary to analyze the changes that have taken place in public procurement after the introduction in 2020 of a new version of the Law of Ukraine "On Public Procurement", as along with the positive aspects are negative, which is manifested in the existence of corruption schemes in tenders. In addition, it is important to identify possible negatives in cooperation with the EU in the introduction of a localization mechanism in Ukraine for tender procurement.
Keywords: публичные финансы, тендерные закупки, Европейский Союз, Польша, Украина